HUBUNGAN PENGGUNAAN GADGET DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA NERS TINGKAT II STIKes SANTA ELISABETH MEDAN TAHUN 2019 - Samfriati S; Lilis N; Mercy N G (Elisabeth Health Jurnal, 2019)
Academic procrastination is one of the postponement behaviors in lecture activities that are often found in students, in this study respondents experiencees a high level of procrastination that could hamper academic activities. One of the causes of procrastination is the use of gadgets that are too long to play games, music, entertainment and so on. Goals : The purpose of this study is to find out the relationship between the use of gadgets and academic procrastination onNursing Students level II Saint Elisabeth Medan 2019. Method : The study design is Cross Sectional. Total sampling technique sample are112 students. The measuring instrument used is a questionnaire. Result : The results shows that the majority of use of positive gadgets (92.9%) and moderate academic procrastination (63.4%). Based on the Fisher's Exact Test, it obtained p-value 0.026 (p <0.05), thus indicating a relationship between the use of gadgets and academic procrastination on nursing students level II STIKes Saint Elisabeth Medan. Conculsion: It is expected that respondents will be able to manage time well and not use gadgets for a long time for things that are not useful. Respondent s are expected to use gadgets for things that can support learning activities.